2011 IEEE SENSORS Proceedings 2011
DOI: 10.1109/icsens.2011.6127371
|View full text |Cite
|
Sign up to set email alerts
|

Real time and adaptive Kalman filter for joint nanometric displacement estimation, parameters tracking and drift correction of EFFPI sensor systems

Abstract: This paper deals with the optimization of an Extrinsic Fiber Fabry-Pérot Interferometer used for very long term (more than one year) and high precision displacement measurements by a real time and adaptive estimation procedure based on a Kalman filter. By performing a sinusoidal laser diode current modulation, a wavelength modulation is created. The Kalman filter takes into account not only the correction of the measurement drift caused by the resultant Optical Power Modulation, but also the correction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…We demonstrated that a synchronous quadrature demodulation -which allows to extract 2 intensity signals in approximate quadrature I(t) and Q(t) (equations 4 and 5) -coupled with fast and innovative real-time algorithms for instantaneous phase estimation, makes it possible to estimate the displacement of the target (Chawah et al (2011)).…”
Section: Opticsmentioning
confidence: 99%
“…We demonstrated that a synchronous quadrature demodulation -which allows to extract 2 intensity signals in approximate quadrature I(t) and Q(t) (equations 4 and 5) -coupled with fast and innovative real-time algorithms for instantaneous phase estimation, makes it possible to estimate the displacement of the target (Chawah et al (2011)).…”
Section: Opticsmentioning
confidence: 99%
“…There are two common ways to correct or compensate the periodic error to achieve more precise measurement: 1) design a novel optical configuration that eliminates the periodic error inherently [10,11,12,13,14], and 2) use a compensation algorithm applied to the measurement data to correct the periodic error electronically [15,16,17,18,19,20,21,22,23,24]. A novel optical configuration of interferometer would lead vastly large and complicated setup, and be more sensitive to environment.…”
Section: Periodic Errormentioning
confidence: 99%
“…Chawah, et al [23] established a system to estimate the coefficients and correct the error based on a Kalman filter on a computer. However, the measurement data has to be transferred from the data acquisition system (FPGA) to the computer for off-line processing.…”
Section: Ellipse Estimationmentioning
confidence: 99%
See 1 more Smart Citation